Functionalisation of ligands through click chemistry: long-lived NIR emission from organic Er(iii) complexes with a perfluorinated core and a hydrogen-containing shell. Issue 1 (22nd December 2016) - Peng, Y.; Hu, J. X.; Lu, H.; Wilson, R. M.; Motevalli, M.; Hernández, I.; Gillin, W. P.; Wyatt, P. B.; Ye, H. Q.
Abstract : Erbium complexes with a fluorinated organic core shell linked to a hydrogen-containing shell, have been synthesized using the click reaction between erbium(iii ) bis(perfluoro-4-azidophenyl)phosphinate and a series of alkynes. Abstract : Erbium complexes with a fluorinated organic core shell linked to a hydrogen-containing shell, have been synthesized using the click reaction between erbium(iii ) bis(perfluoro-4-azidophenyl)phosphinate and a series of alkynes. The erbium 1.5 μm emission lifetimes in the hydrogen-containing erbium complexes exceed 140 μs, the longest ever reported in hydrogenated organic erbium systems. The visible sensitisation for erbium emission indicates a successful strategy that broadens the usage of non-fluorinated chromophores in organic erbium systems and allows more choices for ligand functionalization with exceptional efficiency for erbium emission.